(3GdLGeY aj TQM GdJMQjQs - (3CHh GdMSjf RjO Hf eMeOs; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdfabGJ s
(3BNQgG (B:s
(3BNQg eHJhQ CKfGA (B" (3HGH GdcJGHI (B" (3bhdg (B: (3eSCdI , hdh Cf QLdkG bGd dYHOg cGf GdYHO eedhckG ddhQKI s
(3GdfSNI HgG MhGTs
(3ef CQHYI CLRGAs
(3cJHJ GdfSNI ddabjI YKeGf Hf Ydi Hf YKeGf cJHJ HYV GdYfhGfGJ HGdMeQg s
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs